2014
DOI: 10.4314/bajopas.v7i1.20
|View full text |Cite
|
Sign up to set email alerts
|

<b>Phytochemical Screening, Antibacterial and Toxicological Activities of <i>Acacia Nilotica</i> Extracts</b>

Abstract: The phytochemical screening, antibacterial and toxicological activities of extracts of the leaves, stem bark and roots of Acacia nilotica were investigated. The phytochemical analyses according to standard screening tests using conventional protocols revealed the presence of tannins and sterols in the leaves stem barks and roots of the plant. Alkaloids were detected only in the leaves. Glycosides, saponins, resins and flavonoids were not detected in the plant. In-vitro agar-diffusion sensitivity tests of crude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
2
2
2
Order By: Relevance
“…This indicated a strong antibacterial potential of A. nilotica against the antibiotic-resistant pathogens tested here, arguably with a novel mechanism of action than other tested antibiotics. The antibacterial results of the current study are in accordance with literature, where extracts of A. nilotica were effective against clinical bacterial isolates of E. coli and Salmonella [ 20 , 21 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This indicated a strong antibacterial potential of A. nilotica against the antibiotic-resistant pathogens tested here, arguably with a novel mechanism of action than other tested antibiotics. The antibacterial results of the current study are in accordance with literature, where extracts of A. nilotica were effective against clinical bacterial isolates of E. coli and Salmonella [ 20 , 21 ].…”
Section: Resultssupporting
confidence: 91%
“…The MIC values of acacia leaves and bark extracts against multidrug-resistant E. coli were lower in the current study than previously reported for E. coli , causing otitis infection [ 22 ]. The leaves and bark extracts in the current study also showed lower MIC value against Salmonella typhimurium than previously reported for Salmonella typhi [ 21 ]. The reported differences might be due to different strains of E. coli and Salmonella , and/or different experimental protocols.…”
Section: Resultscontrasting
confidence: 50%
“…The zones of inhibition exhibited by the crude extract against the test isolates ranged between 10 mm and 18 mm. The results support previous reports on the antibacterial activity of this plant (Banso, 2009;Okoro et al, 2014;Abdulhamid et al, 2019). Thus, the pod extract of Acacia nilotica appears to be a potential source of antibacterial compounds that could be relevant in the treatment of infections caused by these organisms.…”
Section: Discussionsupporting
confidence: 91%
“…The use of oil from the seeds is of potential economic benefit to the poor native population of the areas where it is cultivated. Despite that previous studies reported that the different parts of the plant were not toxic to human [12], the seed oil of A. nilotica could be a new source of edible vegetable oil after the future toxicological studies. The 26-ethylcholesta-5,25(Z)-dien-3.β-ol structure was elucidated just by mass spectra and the most possible and inexhaustible structure was determined for this phytosterol.…”
Section: Discussionmentioning
confidence: 86%